Mechanical behavior of electrophoretically modified CFRP composites at elevated temperatures: An assessment of the influence of graphene carboxyl bath concentration. Issue 46 (23rd July 2021) - Gangineni, Pavan Kumar; Patnaik, Satyaroop; Prusty, Rajesh Kumar; Ray, Bankim Chandra
Abstract: The study aims at investigating the mechanical behavior of carbon fiber reinforced polymer (CFRP) composites modified with graphene carboxyl at elevated temperature (ET‐110°C) and understanding the effect of electrophoretic deposition bath concentration (0.5 g/L, 1.0 g/L, and 1.5 g/L) on their mechanical behavior at ET. The 1.5 g/L composite has revealed a maximum improvement in energy absorbed before failure of 33.25% at RT and 22.54% at ET for flexural testing and ∼35% at RT for short beam shear testing, over neat CFRP composite. The modified composites have shown an improved flexural strain to failure at both RT and ET, with 1.5 g/L composite exhibiting maximum enhancement of 12.41% at RT and 26.52% at ET over neat composite. However, at ET, modified composites exhibited lower flexural strength and interlaminar shear strength values in comparison to that of neat. Viscoelastic behavior of all composites was studied to understand bath concentration's effect on thermal behavior via dynamic mechanical thermal analysis. Differential scanning calorimetry was employed for governing the glass transition temperature of composites. Fractography of tested samples (both ET and RT) was performed utilizing a scanning electron microscope to determine the prominent failure mode. Abstract :